Familial Bell's Palsy: A Case Report and Literature Review. (5th August 2012) - Kubik, Mark; Robles, Liliana; Kung, Doris
Abstract : Objective . To describe a unique case of familial Bell's palsy and summarize the current literature regarding possible hereditary influences. Design . Case report. Main Outcome Measures . Clinical exam, CSF analysis, and family history provided per the patient. Results . We report the case of a 58-year-old female who presented with recurrent and bilateral episodes of facial palsy. The patient underwent multiple CSF investigations to rule out a possible infectious and rheumatologic etiology that were all negative. Further questioning revealed she was one of seven family members with a history of unilateral facial nerve paralysis. Conclusion . The sheer number of similar case studies to date suggests that familial clustering of Bell's palsy is a real, noncoincidental phenomenon. Our case represents a unique and perplexing example of one such family. Familial Bell's palsy may represent an autoimmune disease secondary to inherited HLA alloantigens or a structural predisposition to disease based on the dimensions of the facial canal.